Therapeutic Targeting of PPARγ in Nonalcoholic Fatty Liver Disease: Efficacy, Safety, and Drug Development - Zhou Z; Jin R; Gu Y; Ji Y; Lou Y; Wu J (Drug Design, Development and Therapy)
Zhanyi Zhou,1,* Rijuan Jin,1,* Yuting Gu,1 Yunxi Ji,2 Yijie Lou,1 Jianbing Wu3 1The First School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China; 2Department of General Practice, Zhejiang Provincial Hospital of Traditional Chinese Medicine, Hangzhou, Zhejiang, People’s Republic of China; 3Key Laboratory of Drug Prevention and Control Technology of Zhejiang Province, Zhejiang Police College, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianbing Wu, Zhejiang Police College, Hangzhou, Zhejiang, People’s Republic of China, Email wujianbing@zjjcxy.cn Yijie Lou, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China, Email yijie_lou@zcmu.edu.cnAbstract: Non-alcoholic fatty liver disease (NAFLD) is a metabolic-associated liver disorder characterized by a multi-faceted pathological progression involving fat accumulation, oxidative stress, and inflammation. Peroxisome proliferator-activated receptor gamma (PPARγ), a key nuclear receptor involved in lipid metabolism, insulin sensitivity regulation, and immune modulation, plays a significant role in both the development and treatment of NAFLD. This review summarizes the physiological functions of PPARγ in tissues such as adipose tissue, pancreas, intestine, and liver. Furthermore, it compiles current clinical research progress on PPARγ agonists, including mono-agonists, dual agonists, and pan-agonists, and analyzes their associated side effects, mechanisms of occurrence, and potential solutions. Importantly, therapeutic strategies targeting PPARγ hold promise for improving steatosis and insulin resistance and inhibiting liver fibrosis. Future research is needed to further explore the influence of blood insulin levels, hepatic PPARγ levels, and tissue-specific factors on the therapeutic efficacy of PPARγ agonists. Besides, the development of novel PPAR multi-agonists, partial PPARγ agonists, and combination therapies should be explored to optimize therapeutic outcomes while minimizing adverse effects, thereby providing new directions for precision medical interventions in NAFLD.Keywords: PPARγ, NAFLD, therapeutic efficacy, adverse effects